An illustrated key to the Afrotropical bark beetle species of Cladoctonus Strohmeyer (Curculionidae, Scolytinae)—a genus of rare cossonine look-alikes - Jordal, Bjarte H. (Zootaxa, 2024)
The Afrotropical species of Cladoctonus Strohmeyer, 1911 is revised. A key to species is provided with all species illustrated with photos. Five species are currently recognized as valid. Variation between species is limited and samples are few, not yet allowing for assessment of potential intraspecific variation. One synonym is suggested for Cladoctonus affinis Strohmeyer, 1911 (=Cladoctonus eggersi Wichmann, 1911, syn. nov.)